Early detection of autism in primary healthcare in Iceland : parental experience of the procedure and services provided for toddlers, following a positive screening - María Lovísa Breiðdal 1994- (2024)
This exploratory study examined the characteristics of children, referred to the Counselling and Diagnostic Centre (Ráðgjafar og greiningarstöð; RGR) following an 18-month healthcare check-up if autism is suspected. A high-likelihood group of children who underwent this recently implemented approach was examined along with parents’ experience of the process. We examined the percentage of 18-month-old children, who screened positive on the screening tool Modified Checklist for Autism in Toddlers, Revised with Follow-Up (M-CHAT-R/F), met diagnostic criteria for autism before age 5 years old, and explored the characteristics (e.g. age at first signs of autism, who first had concerns about development…) of the children and their families who underwent this early screening process and the services they have received subsequently. Participants comprised 69 children referred to RGR following the screening in the 18-month check-up, as well as an assessment of parents’ (N = 42) experience of the screening process. RGR’s existing data and a parent survey designed by the researchers were used to conduct the study. Most of the children (65%) had completed the diagnostic process, with 86% of them diagnosed with autism. The average diagnosis age was 2.5 years, and the average waiting period was 1.2 years. Parents were generally satisfied with the service provided after the screening in an 18-month check-up, but satisfaction with that service did not significantly affect their attitudes towards the early screening process: (x2(4) = 6.05, p = .196). Most (84%) of the parents had positive attitudes toward the process, but diagnostic status did not significantly affect their attitudes toward the process: (x2(2) = 1.88, p = .391). Taken together, the M-CHAT-R/F proved effective in detecting early autism signs among 18-month-olds in healthcare check-up, and parents were generally satisfied with the early screening process during this standard healthcare visit. Keywords: autism, 18-month-old check-up, screening, M-CHAT-R/F, early ...